Yes, Eliminative Materialism Is Self‐Defeating. (15th November 2019) - Slagle, Jim
Abstract: Eliminative materialism seeks to replace our familiar categories of mentality, "folk psychology, " with those of cognitive science. One of the objections to this project has been that is self‐defeating. Any attempt to argue for, defend, present, or even contemplate eliminativism in one's own mind can only get started by employing the very categories it decries. Counterarguments to this objection include that to accuse eliminativism of being self‐defeating begs the question (the Churchlands) and that it can be reduced to other objections to eliminativism (Ramsey). I argue that these counterarguments are unsuccessful and that eliminativism is in fact self‐defeating.